A Comparison of Microplastic in Fish From Australia and Fiji - Wootton, Nina; Ferreira, Marta; Reis-Santos, Patrick; Gillanders, Bronwyn M. (Frontiers in Marine Science, 2021)
Awareness surrounding plastic pollution has increased significantly in the past decade, leading to concerns on potential adverse effects on biota, including the consumption of microplastic by fish. Globally, plastic has been found in many species of fish, but little research has been undertaken in the southern hemisphere. We assessed the abundance and type of plastic in fish captured and sold for human consumption in Australia and Fiji. Fish (goatfish, sea mullet, paddletail, and common coral trout) had their gastrointestinal tracts dissected and microplastic quantified under a microscope. Plastic polymer types were confirmed using μ-FTIR. In Australia, plastic was found in 61.6% of fish gastrointestinal tracts, while in Fiji, 35.3% of fish had plastic. Fish from Australia had almost double the amount of plastic on average than fish caught in Fiji, with 1.58 (± 0.23) pieces per fish in Australia compared to 0.86 (± 0.14) in fish caught in Fiji. The types of plastic differed between countries, with fibers comprising 83.6% of microplastic pieces in fish from Australia whereas 50% of microplastic found in fish from Fiji was film. Polyolefin was the most abundant polymer type in both fibers from Australia and film from Fiji. We hypothesize variations in abundance and plastic type are a reflection of the population density and coastal geomorphology, but may also be a result of legislation and waste management strategies in the two countries. This work adds evidence to the pervasive presence of plastic in fish gastrointestinal tracts, reinforcing the urgent need for efficient plastic waste management, but also a better understanding of the impacts of microplastic on marine biota.